The Role of Self-Efficacy and Emotional Support on Teacher-Student Relationships among Special Guidance Teachers at Muhammadiyah Inclusive Schools in Sidoarjo : Peran Efikasi Diri dan Dukungan Emosi terhadap Relasi Guru Siswa pada Guru Pembimbing Khusus di Sekolah Inklusi Muhammadiyah Kabupaten Sidoarjo - Nurfi Laili; Vanda Rezania; Eko Hardi Ansyah (Academia Open, 2025)
A positive teacher-student relationship model can improve student self-efficacy, especially for those with special needs. Self-efficacy, which is students' belief in their ability to complete tasks, is strongly influenced by interactions with teachers. Teachers who provide emotional support play a significant role in strengthening students' self-efficacy, helping them overcome learning challenges, and encouraging active participation in the educational process. This study aims to model the relationship between teacher-student relationships, self-efficacy, and emotional support among special guidance teachers teaching in inclusive schools. The population in this study was 50 special guidance teachers teaching in Muhammadiyah inclusive schools in Sidoarjo Regency. The sampling technique used was saturated sampling. The measuring instruments used were the Teacher Student Relationship Scale (TSRS), an adaptation of the General Self-Efficacy to measure teacher self-efficacy, and the Teacher Emotional Support Scale (TESS), especially in the emotional support domain from the theory of Hamre & Pianta (2009). Data analysis used regression analysis to examine the relationship and influence between variables. The software used in this analysis was JASP. The targeted output is acceptance in Intuition: Journal of Scientific Psychology (S3) and IPR of research results posters. Highlights: Positive teacher-student relationships strengthen self-efficacy in inclusive settings. Emotional support is a key factor in overcoming learning challenges. Regression analysis reveals interconnections among relationship, support, and efficacy. Keywords: Emotional Support; Inclusive School; Self-Efficacy; Teacher Student Relationship; Special Guidance Teacher